Window to wall ratio and orientation effects on thermal performance of residential building: A case of Butwal Sub-Metropolis - Uprety, Sanjaya; Kafley, Shiva; Shrestha, Barsha (Journal of Engineering Issues and Solutions, 2021)
The orientation and glazed surface area used for windows in a building have significant effects on its indoor thermal comfort and overall energy consumption. The increasing use of glazed windows and lack of consideration of orientation in building design have become a major problem in warm and humid regions as windows cover sensitive skin areas for the exchange of energy leading to increased solar gain inside the building. This paper describes the effect of the varied ‘area ratio of glazed window to the wall for different building orientations’ on the thermal performance of the residential building in a warm humid climatic region of Nepal. A typical residential building located in Kalikanagr of Butwal, the fast-urbanizing sub-metropolis of Western Nepal, was selected for the study from 18 houses surveyed using the purposive sampling method. Nine varying values of Window to Wall Ratio (WWR) of glazed façade ranging from 0.1 to 0.9 with a constant increment of 0.1 in north and south façades, and the change in the building orientations were considered for the detailed study. Altogether eighty different test scenarios including base case scenarios were created and annual thermal energy consumption was computed for each test scenario using the Autodesk Ecotect Analysis, 2011. Findings from the study showed that the south orientation is the most appropriate compared to the north-east for all WWR to reduce the building energy consumption and an increase in WWR also results in increased energy consumption. The study concludes the careful considerations of WWR and the south orientation during the designing of building will contribute to efficient energy consumption in residential buildings.